Lowland rice soil classification at village Sukorejo subdistrict Sei Balai, district of Batubara based on soil taxonomy 2014 - hamdi fadli kurniawan; purba marpaung; Jamilah Jamilah (Jurnal Agroekoteknologi, 2018)
Classification of soil is a process to select the soil according to the characteristic and their ability. Classification gives a description of the physical properties, chemistry, and minerals of land owned which can then be used as a basis for management for land users. The study aim to classify the soils on orders, sub orders, great groups and sub groups. The location at Village Sukorejo Subdistrict Sei Balai District Batubara, that start from September 2016 until Januari, 2017. Soil morphology was description of soil profiles to know soil properties, horizons and diagnostic horizon. Soil samples were taken from each horizon for laboratory analysis of soil texture, bulk density, pH (H2O), pH (KCl), P2O5, organic carbon, exchangeable cations (Ca2+, Mg2+, K+, Na+), Total Fe, Al can be exchange, base saturation and cation exchange capacity (CEC) in Socfindo, Asian Agri, and Chemistry and Soil Fertility Laboratories Agriculture Faculty University of North Sumatera. The results shows that type of soil SPL 1A and 1B are Ultisols, Aquults, Albaquults, dan Typic Albaquults. For SPL 2A and 2B are Inceptisols, Aquepts, Endoaquepts, dan Aquandic Endoaquepts.  Keywords : Lowland rice, soil classification, soil taxonomy 2014